2022
DOI: 10.1097/wad.0000000000000484
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Decision-making Capacity and the Domains of Awareness in Alzheimer Disease

Abstract: People with Alzheimer dementia (PwAD) who are aware of their overall cognitive function and diagnosis are more likely to be judged competent in decision-making capacity. Therefore, we aimed to investigate the relationship between decision-making capacity and the different domains of awareness and the relationship between decision-making capacity and the cognitive and clinical impairment of the PwAD. Using a cross-sectional design, we included 121 PwAD and their caregivers. Awareness was assessed across domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Residents identified the need for assistance with decision-making due to memory impairments in the theme “Reliance on NH Staff and Family.” Within this theme some residents described needing support in decision-making around preferences for everyday living including reminders to use assistive devices. This may indicate continued decision-making capacity which is supported by recent research suggesting awareness of disease progression may indicate higher levels of decision-making capacity of residents with ADRD 21 . Clinicians can support residents in communicating decisions about their treatment by conducting decision-making capacity assessments.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Residents identified the need for assistance with decision-making due to memory impairments in the theme “Reliance on NH Staff and Family.” Within this theme some residents described needing support in decision-making around preferences for everyday living including reminders to use assistive devices. This may indicate continued decision-making capacity which is supported by recent research suggesting awareness of disease progression may indicate higher levels of decision-making capacity of residents with ADRD 21 . Clinicians can support residents in communicating decisions about their treatment by conducting decision-making capacity assessments.…”
Section: Discussionmentioning
confidence: 81%
“…This may indicate continued decision-making capacity which is supported by recent research suggesting awareness of disease progression may indicate higher levels of decision-making capacity of residents with ADRD. 21 Clinicians can support residents in communicating decisions about their treatment by conducting decision-making capacity assessments.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The ASPIDD scores reflect four degrees of awareness (preserved, mildly impaired, moderately impaired, and absent), while clinicians’ ratings only present three degrees (preserved, impaired, and absent). We found that clinicians’ ratings could not distinguish between the mildly and moderately impaired awareness groups, which has important implications for care, especially regarding autonomy and decision-making capacity, involving patients’ decisions on treatment, institutionalization, and management of their property [ 16 ]. This aspect may limit the measurement’s sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Appelbaum and Grisso [ 15 ] allude to four decision-making capacities: communicating consistently, understanding choices, evaluating implications and consequences, and reasoned estimates of risks and benefits. A recent study [ 16 ] showed that decision-making capacity is related to the cognitive and functional domains of awareness and is relatively independent of the emotional functioning and relationship domains. PwAD who are unaware of their disease or of their cognitive and functional impairments may be unlikely to appreciate the personal benefits of an alternative or to accurately understand and judge the consequences of a decision.…”
Section: Introductionmentioning
confidence: 99%